Research and architectural conservation in Marina el-Alamein in 2018 (Polish–Egyptian Conservation Mission) - Grażyna Bąkowska-Czerner; Rafał Czerner (Polish Archaeology in the Mediterranean, 2019)
Activities undertaken by the Polish–Egyptian Conservation Mission to Marina el-Alamein in 2018 comprised research and conservation mainly in the public district of the ancient town and, additionally, in private houses. Work focused foremost on research and presentation of remains of two streets, running east and south of the southeastern corner of the main town square, and the adjoining monuments. Research and conservation continued also on the remains of public Roman baths dating from the 1st to the 3rd century AD, located in the area south of the square. Maintenance conservation was carried out in Houses H21c and H1 and in the ancient town center. Land grading to enhance exhibition value and ensure rainwater drainage was carried out in some areas.